(untitled) (Journal of Economic Research & Business Administration, 2015)
The agroindustrial complex is a diversified system, which includes agriculture, economic industries of production for agriculture, manufacturing and infrastructure. In order to assess the competitiveness of agribusiness must consider the whole range of factors and indicators characterizing its constituent industries. The article presents the different points of view on the definition of the level of competitiveness of agroindustrial enterprises in terms of integration. The analysis of the food industry - a major agribusiness industry, which depends on the functioning of the country’s food security in the context of globalization. The factors and conditions for competitive development of the industry were identified. For strengthen competitive advantages of the agricultural sector of Kazakhstan needs to develop agricultural machinery, which is an important priority segments of the national economy in terms of integration. This sector and the activities undertaken to improve the competitiveness of agricultural engineering were analyzed.